Prevalence and correlates of diagnosed and undiagnosed hypertension in the indigenous Kuna population of Panamá - Daniel R. Hanna; Rebekah J. Walker; Brittany L. Smalls; Jennifer A. Campbell; Aprill Z. Dawson; Leonard E. Egede (BMC, 2019)
Abstract Background To determine the prevalence of hypertension and investigate sociodemographic correlates in an indigenous Kuna community living on the San Blas islands of Panama. Methods Data was collected from adults using a paper-based survey using a cross sectional study design. Blood pressure was measured, and hypertension defined at two cut-points: 130/80 mmHg and 140/90 mmHg. Individuals with undiagnosed hypertension had a blood pressure measurement that indicated hypertension, however, the individual had not been told by a doctor they had hypertension. Whereas individuals with diagnosed hypertension had been told by a healthcare provider that they had hypertension. Univariate tests compared diagnosed and undiagnosed hypertension by sociodemographic categories and logistic regression models tested individual correlates adjusting for all sociodemographic factors. Results Two hundred and eleven adult indigenous Kuna participated in the study. Overall prevalence of hypertension was 6.2% (95%CI:3.32-10.30) as defined by 140/90 mmHg, and 16.6% (95%CI:11.83-22.31) as defined by 130/80 mmHg. Hypertension was significantly higher in men (31.6, 95% CI:19.90-45.24, compared to 11.0, 95% CI:6.56-17.09). Individuals with low income were 3 times more likely to be hypertensive (OR = 3.13, 95% CI:1.02-9.60) and 3.5 times more likely to have undiagnosed hypertension (OR = 3.42, 95% CI:1.01-11.52); while those with moderate income were 6 times more likely to be hypertensive (OR = 7.37, 95% CI:1.76-30.90) compared to those who were poor. Conclusion The prevalence of diagnosed and undiagnosed hypertension is higher in men and those with higher income. Investigating these factors remains vitally important in helping improve the health of the Kuna through targeted interventions to address chronic disease.